La naturaleza jurídica de la adjudicación de los Bienes Inmuebles que poseen título de dominio en el Sector Rural dentro de la Provincia de Chimborazo - Flores Delgado, Ana Luisa (2019)
The Undersecretary of Lands and Agrarian Reform, is the institution responsible for the securitization of lands to those who lack of propetary titles and who are in possession of the petitioners, for this purpose, the corresponding administrative act must be followed in base to the Organic Law of Rural Lands and Ancestral Territories, its regulations and the Manual of Procedures and Administrative Procedures of Rural Lands. Once the administrative act has begun, it is vital important that the institution verifies the legality and veracity of the information, to avoid future problems in relation to the securitization of the assets that are intended to be awarded. However, there are flaws not only by the institution in charge of the administrative act but by various institutions that grant certifications without adequate control. In this way, it is possible that, on a property, there are several owners with totally different property titles, causing a violation of the right to private property to which they have access, a situation that brings various social and legal problems towards the owners the subject matter of litigation.